HUBUNGAN OBESITAS DENGAN KUALITAS HIDUP WANITA USIA SUBUR (WUS) DI WILAYAH KERJA PUSKESMAS INGIN JAYA ACEH BESAR - Rimadeni, Yeni; Munazar, Munazar; Warnidar, Eka; Surya, Erdi (Universitas Muhammadiyah Sumatera Utara, 2022)
Weight gain can put you at risk of developing non-communicable diseases. Even during this pandemic, obesity is one of the risk factors associated with an increase in COVID-19 infection. However, the implementation of Community Activity Restrictions (PPKM) caused a lack of activity during COVID-19 and irregular eating patterns caused them to gain weight. In addition, obesity has an impact on a decreased quality of life. The purpose of the study was to determine the average increase in body weight during the covid pandemic and the relationship between obesity and the quality of life for women. The design of this research is cross-sectional. The research was conducted at the Ingin Jaya Health Center in August. Sources of data used are primary data and secondary data. The sample in this study were women of childbearing age (WCBA) in the work area of the Ingin Jaya Health Center, Aceh Besar. The results of this study are the average weight value of WCBA before the covid pandemic is 56.48 kg and during the covid pandemic it is 59.46 kg. There is a relationship between education and work variables on the quality of life in women of childbearing age (WCBA) in the work area of the Ingin Jaya Health Center